Intracranial solitary fibrous tumors: a heterogeneous entity with an uncertain clinical behavior - Gubian, Arthur (World neurosurgery, 2019)
Background - Intracranial solitary fibrous tumors (ISFTs) are rare mesenchymal neoplasms originating in the meninges and characterized by very different biologic and clinical behaviors. Benign histotypes, such as hemangiopericytomas, are now considered a cellular phenotypic variant of this heterogeneous group of rare spindle-cell tumors. Owing to their rarity and resemblance to other, more common brain tumors, ISFTs are often poorly recognized and remain a diagnostic challenge. - Methods - We describe a surgical series of 29 patients treated for ISFTs confirmed histologically and through immunohistochemistry. We attempt to provide a focus on the natural history of these pathologies and the need for tailored management. - Results - This was a retrospective consecutive series of 29 patients with either solitary fibrous tumor (n = 14) or hemangiopericytoma (n = 15) over a 10-year period. Mean follow-up time was 37.71 months. Recurrence rate was 42.9% for solitary fibrous tumors versus 26.7% for hemangiopericytomas. STAT6 expression was 66.7% in hemangiopericytomas versus 42.9% in SFTs. - Conclusions - Histopathology and immunohistochemical staining (characterized by positive expression of mainly STAT6 but also CD34, Bcl-2 protein, and vimentin) are key in diagnosis and management of ISFTs. Although ISFTs are still considered benign lesions with very rare aggressive evolution, their clinical behavior is largely unpredictable. This study highlights the importance of relying on immunohistochemistry for a thorough definition of the management strategy.